Tuning the ionic character of sodium dodecyl sulphate via counter-ion binding: An experimental and computational study - Pérez-Sánchez, Germán; Schaeffer, Nicolas; Greaves, Tamar L.; Pereira, Jorge F. B.; Coutinho, João A. P. (Frontiers in Materials, 2022)
Solutions of surfactants exhibit remarkable features, such as a tunable amphiphilic character, which can further be varied for ionic surfactants through variations in their Coulombic interactions. These properties are very useful in many industrial applications such as in extraction, purification, and formulation processes, as detergents, wetting agents, or emulsifiers. Rather unexpectedly, the addition of tetrabutylammonium chloride ([N4,4,4,4]Cl) to solutions of the ionic surfactant of sodium dodecyl sulphate (SDS) results in the appearance of a lower critical temperature (LCST) phase transition, a property usually associated with non-ionic surfactants. The aim of this study is to provide a detailed nanoscopic scenario on the interaction between SDS micelles and [N4,4,4,4]Cl moieties to better understand the nature of the LCST cloud point and how to confer it to a given ionic surfactant system. A coarse-grained molecular dynamics (CG-MD) computational framework, under the latest MARTINI 3.0 force field, was developed and validated using available literature data. The impact of [N4,4,4,4]Cl concentration in the phase of SDS micellar aqueous solutions was then characterized and compared using experimental results. Specifically, dynamic light scattering (DLS) measurements and small-angle X-ray scattering (SAXS) profiles were obtained at different [N4,4,4,4]+/[DS]- molar ratios (from 0.0 to 1.0) and compared with the CG-MD results. A good agreement between computer simulations and experimental findings was obtained, reinforcing the suitability of GC-MD to simulate complex phase behaviors. When the [N4,4,4,4]+/[DS]- molar ratio is < 0.5, a weak impact of the cation in the micellar distribution was found whereas for ratios > 0.5, the system yielded clusters of enclosed small [DS]- aggregates. Thus, the CG-MD simulations showed the formation of mixed [DS]- and [N4,4,4,4]+ aggregates with [N4,4,4,4]+ cations acting as a bridge between small [DS]- micelles. The CG-MD simulation framework developed in this work captured the role of [N4,4,4,4]+ in the micellar phase transition whilst improving the results obtained with preceding computer models for which the limitations on capturing SDS and [N4,4,4,4]Cl mixtures in aqueous solutions are also shown in detail.